Numerical Model of CAI Test for Fibre-Reinforced Polymer Plate. - Baszczyński, Piotr; Dziomdziora, Sebastian; Naze, Rafał; Kubiak, Tomasz (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2016)
This article presents numerical simulations of laminates subjected to Compression After Impact (CAI) testing including delamination modelling. Different model of impact damages of laminate were considered. Progressive damage analysis have been employed and different failure criteria have been applied. For each simulation failure load has been estimated as same as the position of damages at destroyed layer. Finally, obtained numerical results were compared with experimental data from referential paper.
Keywords: CAI; numerical simulations; FEM; FRP laminates; compression after impact; finite element method; kompresja po uderzeniu; symulacja numeryczna; metoda elementów skończonych; laminaty wzmocnione włóknem szklanym z poliestru